2005
DOI: 10.1111/j.1475-4762.2005.00636.x
|View full text |Cite
|
Sign up to set email alerts
|

Local provenance in rehabilitation of degraded landscapes: a case study from the Hawkesbury–Nepean catchment, Australia

Abstract: Throughout Australia thousands of volunteers are engaged in Landcare projects that should help rehabilitate degraded landscapes. Many of these projects involve tree planting, but their seed is not necessarily of local provenance. Based on a survey of 85 Landcare groups working in the Hawkesbury–Nepean catchment, data were collected about Landcare groups’ knowledge of their seed source, understanding of local provenance and the ecosystem in which they were planting trees and the source of funding for their proj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…Burgin et al [50] observed that there were some 1500 such groups across New South Wales addressing issues such as weed control, revegetation, soil erosion by water, stream bank erosion and river or estuary corridor degradation. They found that approximately one third of people surveyed participated in 'environmental restoration activities', although rural residents were more likely to undertake such activities than those with an urban background.…”
Section: Discussionmentioning
confidence: 98%
“…Burgin et al [50] observed that there were some 1500 such groups across New South Wales addressing issues such as weed control, revegetation, soil erosion by water, stream bank erosion and river or estuary corridor degradation. They found that approximately one third of people surveyed participated in 'environmental restoration activities', although rural residents were more likely to undertake such activities than those with an urban background.…”
Section: Discussionmentioning
confidence: 98%
“…The focus of Landcare is to more sustainably manage natural resources and the network encompasses a range of 'care' groups that reflect the interests of the participants (e.g., Rivercare, Dundcare, Bushcare; Burgin et al 2005). In December 2010, in New South Wales alone, there were 2130 groups (57,454 individuals) registered under Landcare (LandcareNSW 2011), and communities in each state and territory participate (Burgin et al 2005). In 2010, Clear Up Australia Day attracted 588,000 volunteers (1 in 50 Australians) to remove rubbish from 7,000 registered sties (Landcare Australia Ltd, undated).…”
Section: Discussionmentioning
confidence: 99%
“…Where the 'improvement' includes plantings, these are likely to be of different provenance to local species and thus have the potential to interfere with the genetic integrity of the local endemic vegetation (Burgin et al 2005). Such plantings are also generally a subset of late succession species that ultimately change the structure and composition of the area (Burgin 2002).…”
Section: Flawed Logic Of the Offset Processmentioning
confidence: 99%